An approach to the legal requirements regarding railway transport safety monitoring in the European Union - Sitarz, Marek; Chruzik, Katarzyna (Transport, 2019)
The targeted liberalisation of the European Union railway market in 1998 could have lead to a decrease in the safety of rail transport. To prevent this, the European Commission developed and implemented new requirements in this area without explicitly deciding on the methods and tools to be used for their implementation. Entities operating in the market faced a new challenge, the development of a systems model approach to safety management. Only a correctly designed process model, along with the appropriate tools for monitoring and managing risk, allows the level of safety to be maintained at current levels or improved. As part of the research, solutions were developed for a systems approach to safety management in railway transport and the risk management and maintenance monitoring of railway vehicles. Safety is an essential criterion for assessing the functioning of a railway system, it determines its efficiency as well as – in a widely understood sense – the quality of its transport services. This paper describes the legal requirements and practical methods of implementation arising from the issue of Directive 2004/49/EC as it concerns the monitoring of railway safety (Chruzik et al. 2014). The directive enforces the gradual introduction of Common Safety Targets (CST) and Common Safety Methods (CSM) to maintain (or increase) the existing high safety levels after the opening up (liberalisation) of the rail market. The introduction of CST and CSM necessitates the development of methods for the evaluation of the level of safety and activity of operators, both at the level of the Member States and also at the level of the European Union. The paper describes the practical solutions developed for railway operators as part of the implementation of maintenance management systems (Sitarz et al. 2013; Chruzik et al. 2014).